Global Challenges in Elementary Qur’an Memorization - Khotimah, Husnul; NIisak, Nur Maslikhatun (Indonesian Journal of Islamic Studies, 2024)
Memorizing the Qur’an is a significant religious achievement, especially during elementary school years. However, students at SD Muhammadiyah 1 Sedati face difficulties in this regard. This study explores these challenges, focusing on factors like age, academic workload, and family support. Through qualitative methods including interviews and questionnaires, it was found that these factors significantly affect students' cognitive abilities and comprehension of the Al-Quran text. The study aims to provide insights for educators, parents, and policymakers to improve Qur’an learning at the elementary level, thus enhancing students' religious achievements and overall development. Highlight: Age, workload, family impact memorization. Understanding challenges crucial for improvement. Insights enhance religious achievements and development. Keywords: Qur’an memorization, elementary school, challenges, religious education, Muhammadiyah 1 Sedati.